2014
DOI: 10.1007/s11356-014-3619-8
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and nickel in blood of Tunisian population and risk of nasosinusal polyposis disease

Abstract: Nasosinusal polyposis (NSP) is a chronic inflammatory disease of the nasal mucosa. Although the pathophysiology underlying NSP formation is not fully understood, environmental factors appear to be contributed the development of this disease. A case-control study of Tunisian patients was examined to assess the levels of cadmium (Cd) and nickel (Ni) in blood and reparse the association between the exposure to these metals and the risk of nasosinusal polyposis disease. Mean blood levels of Cd in patients (2.2 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Twelve studies used a case-control study design. 7,15,[28][29][30][31][32][33][34][35][36][37] A cross-sectional design (n = 12) was also used in many studies. [38][39][40][41][42][43][44][45][46][47][48][49] Other study designs included a quasi-experimental design (n = 3), [50][51][52] a time series (n = 2), 14,53 cohort (n = 2), 54,55 single group pretest-postest (n = 2), 56,57 experimental (n = 2), 58,59 a crossover design (n = 2), 60,61 secondary analysis (n = 1), 62 repeated measures (n = 1), 63 and case report (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies used a case-control study design. 7,15,[28][29][30][31][32][33][34][35][36][37] A cross-sectional design (n = 12) was also used in many studies. [38][39][40][41][42][43][44][45][46][47][48][49] Other study designs included a quasi-experimental design (n = 3), [50][51][52] a time series (n = 2), 14,53 cohort (n = 2), 54,55 single group pretest-postest (n = 2), 56,57 experimental (n = 2), 58,59 a crossover design (n = 2), 60,61 secondary analysis (n = 1), 62 repeated measures (n = 1), 63 and case report (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…No significant association has been found between high nickel blood levels and the risk of nasosinusal polyposis in a case–control study of Tunisian patients (Khlifi et al., 2015) and between serum nickel concentrations and brain damage markers and serum hormones in a case–control study with male Russian patients suffering from acute ischaemic stroke (Skalny et al., 2017). In Chinese pregnant women, a significant association was observed for nickel in blood with a decrease in free thyroxine using single‐metal models.…”
Section: Assessmentmentioning
confidence: 99%
“…In a case report in 2014, it is observed that a 26-years-old chemist working with Ni nanoparticles has facial flushing and upper airway symptoms such as nasal congestion, throat irritation and post nasal drip [9]. A study which is performed by Khlifi et al suggests that toxic heavy metals such as cadmium and Ni have possible effects on development of nasosinusal polyposis disease [10]. Various long term studies have provided different results about the relationship between Ni exposure with lung and nasal cancers [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%